Functional glycomics - Fukuda, Minoru (Methods in enzymology, 2010)
In this 3 volume collection focusing on glycomics, readers will appreciate how such discoveries were made and how such methods can be applied for readers' own research efforts Each chapter has been designed so that enough scientific background will be given in each chapter for further development of methods by readers themselves. Useful for all levels of scientists starting from the last years of colleges, graduate students, postdoctoral fellows to professors and to all levels of scientists in research institutes including industry